PENGARUH PEMBERIAN LIMBAH CAIR PABRIK KELAPA SAWIT DAN PUPUK N, P, K TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSERY PADA TANAH PMK - Perdi Perdi; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aimed of this research to get the interaction of liquid waste of palm oil mill and N, P, K fertilizer and get best dosage of them to growth of plam oil seedlingin pre nursery on red yellow podzolic soil. The research conducted on September to December 2016. The research used Completely Randomized Design of factorial that consisting of two factors. The first factor is the liquid waste of palm oil mill (LWPOM), consists of (0, 1.6,1.8, 2.0 l/polybag) andthe second factor is the NPK fertilizer, consists of (Urea 0.34 g Urea + 0.35 g TSP + 0.32 g KCl/polybag), (0.44 g Urea + 0.45 g TSP + 0.42 g KCl/polybag), and                                         (0.54 g Urea + 0.55 g TSP + 0.52 g KCl/polybag). Data obtained from the research were statistically analyzed by analysis of variance followed by a further test of Duncan's New Multiple Range Test (DNMRT) at 5%. Parameters were observed height of seedling, diameter of hums, number of leaf midrib, leaf area, shoot root ratio and dry weight. Giving of liquid waste of palm oil mill and N, P, K fertilizersignificantly to height of seedling, stem diameter, number of leaf midrib. Aplication liquid waste of palm oil mill 2.0 l/polybag and NPK (Urea 0.34 g Urea + 0.35 g TSP + 0.32 g KCl/polybag). Gave the best og growth of palm oil seedilings in pre nursery red yellow podzolic soil. Keywords: Liquid Waste Palm Oil Factory, , Fertilizer N,P,K,  PMK Land,